Mathematical Modeling of Lithium Batteries : From Electrochemical Models to State Estimator Algorithms /: From Electrochemical Models to State Estimator Algorithms. (2017) - Hariharan, Krishnan S; Tagade, Piyush; Ramachandran, Sanoop
No abstract available